2017
DOI: 10.1242/dmm.026682
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting memory deficits in mice withdrawn from cocaine are concomitant to neuroadaptations in hippocampal basal activity, GABAergic interneurons and adult neurogenesis

Abstract: Cocaine addiction disorder is notably aggravated by concomitant cognitive and emotional pathology that impedes recovery. We studied whether a persistent cognitive/emotional dysregulation in mice withdrawn from cocaine holds a neurobiological correlate within the hippocampus, a limbic region with a key role in anxiety and memory but that has been scarcely investigated in cocaine addiction research. Mice were submitted to a chronic cocaine (20 mg/kg/day for 12 days) or vehicle treatment followed by 44 drug-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 124 publications
5
48
0
2
Order By: Relevance
“…Although it should be noted that despite broadly consistent performance, all rats performed incrementally worse over time, a finding that parallels the long‐lasting cognitive deficits that cocaine appears to induce in human (see Rogers and Robbins for review). Long‐lasting deficits have also been reported in other animal studies, although these findings are not unequivocal as a recent study showed that stimulant‐induced deficits were remediated over a time course similar to the one used here . These apparent discrepancies are likely related to differences in inter‐testing training, which can have a pronounced effect on the cognitive process taxed (see Cocker and Winstanley for discussion).…”
Section: Discussionsupporting
confidence: 65%
“…Although it should be noted that despite broadly consistent performance, all rats performed incrementally worse over time, a finding that parallels the long‐lasting cognitive deficits that cocaine appears to induce in human (see Rogers and Robbins for review). Long‐lasting deficits have also been reported in other animal studies, although these findings are not unequivocal as a recent study showed that stimulant‐induced deficits were remediated over a time course similar to the one used here . These apparent discrepancies are likely related to differences in inter‐testing training, which can have a pronounced effect on the cognitive process taxed (see Cocker and Winstanley for discussion).…”
Section: Discussionsupporting
confidence: 65%
“…Control sections run in parallel had omission of the primary antibody. Although we did not conduct pre-adsorption of the antibodies in this study, all of the primary antibodies are well-characterized (Massart et al 2015; Picot et al 2014; Ladron de Guevara-Miranda et al 2017), and expression patterns were entirely consistent with the literature (i.e., labeling was nuclear, with expected distribution). The following day, sections were incubated in anti-rabbit biotinylated secondary antibody (1:500 in blocking solution; Vector Labs, Burlingame, CA, USA) before avidin-biotin conjugate (1:000 in 0.1M PB; Vectastain ABC Elite kit; Vector Laboratories, Burlingame, CA).…”
Section: Methodssupporting
confidence: 60%
“…Sections were then incubated with biotinylated tyramine (1:1000 in 0.1M PB; Perkin Elmer, Waltham, MA) for 10 min, and visualized with Alexa 488-tagged streptavidin (1:400 in 0.1M PB; Life Technologies, Grand Island, NY). After washing thoroughly with 0.1M PB, sections were then incubated with mouse anti-Fos primary antibody (1:600; Santa Cruz Biotechnology sc-271243, RRID: 1563391, Ladron de Guevara-Miranda et al 2017) in blocking solution, overnight at room temperature. The following day, sections were incubated for 60 minutes with Alexa 555 goat-anti mouse secondary (1:400 in 0.1M PB; Life Technologies, Grand Island, NY).…”
Section: Methodsmentioning
confidence: 99%
“…Hippocampal dopamine secretion and uptake mainly originates from adrenergic neurons of the locus coeruleus (LC) 25 , 26 and diffusely targets neurons in the CA1 region 19 . Hippocampus has been implicated as the main “node” in the cocaine addiction brain circuit, potentially through production of new, novel inter-neuronal circuits 27 29 . LC is also known to play an important role in driving drug addiction in response to stress based on its influence on the hippocampus and encoding of novel stimulus memories 30 .…”
Section: Discussionmentioning
confidence: 99%